NEW-WORD FORMATION AND SOCIAL DISRUPTION ON METAVERSE - Simatupang, Ervina CM; Heryono, Heri (University of Kuningan, 2022)
The virtual environments have provided users with varied degrees of digital transformation, despite the fact that users are non-permanent and unconnected. To further assist the digital transition in every element of physical life, the term Metaverse has been coined. It cannot be avoided that language, furthermore linguistics, has involvement to the word framing and word creation within Metaverse. This research is purposed to determine some typical new-word formations or neologisms that impact to the establishment of terminologies within Metaverse. On the other hand, cultural aspect also becomes the concern towards this new universe; since people need to be well-informed in the term of consequence and benefits. The method of the research applied qualitative method and distributional method by Segmenting Immediate Constituents Techniques; which means the technique of dividing a construction of direct elements which form the construction. Three main theories used in this paper are neologism by Kilmer (2020), social disruption by Kumbara et al. (2020) and Metaverse by Mystakidis (2019). The paper puts three different terminologies that are analyzed using linguistic and cultural perspective. Those three words are Persistent Virtual World (PVW), blockchain and NFT that massively arise in the Metaverse terminologies. Based on the analysis, it can be inferred that those terminologies are categorized to morphological and semantic neologism; which also includes abbreviation and broadening. The notion of an immersive Internet as a massive, unified, persistent, and shared realm is at the core of Metaverse.